Continuous twice-impacts analysis of UHMWPE laminate fixed with bolted joints. (November 2017) - Shen, Zhiwei; Hu, Dean; Zhang, Youmin; Cai, Qingyu; Han, Xu
Highlights: Twice-impacts test for UHMWPE laminate fixed with bolted joints is conducted. The simulation model is validated in the first impact and applied to analysis of the second impact. Impact parameters of the second impact are identified based on deformation of bolt holes. The research scheme of this paper provides reference to recognize the process of multi-impacts. Abstract: Generally, the relative parameters of continuous multi-impacts are ambiguous in the practical engineering. In this paper, continuous twice-impacts of Ultra-High Molecule Weight Polyethylene (UHMWPE) laminate which is fixed by four bolted joints are designed and conducted by experiment and simulation. The experimental results of first impact are used to verify the numerical model, in which a solid blunt projectile penetrates the laminate with the velocity of 216 m/s. The obtained results of experiment and simulation indicate that strong lateral effects can be observed for the twice-impacts of UHMWPE target fixed with bolted joints, then the deformation responses of bolt holes are studied to discuss parameters identification of secondary non-penetration impact, i.e., the velocity and impact position of secondary penetrator are identified based on inverse problem model. Finally, the numerical results calculated with the identification parameters are in good agreement with the twice-impacts test. The research scheme of this paper is significant to recognize the process of multi-impacts.